2017
DOI: 10.1097/hpc.0000000000000122
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency, Supplementation, and Cardiovascular Health

Abstract: Vitamin D has been traditionally recognized as a vitamin quintessential for bone-mineral health. In the past 2 decades, numerous experimental and observational studies have highlighted the role of vitamin D in immunity, metabolic syndrome (obesity and diabetes), cancers, renal disease, memory, and neurological dysfunction. In this article, we review important studies that focused on the impact of vitamin D on blood pressure, myocardial infarction, peripheral arterial disease, heart failure, and statin intolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 128 publications
0
23
0
2
Order By: Relevance
“…Many other health benefits are associated with higher 25(OH)D concentrations, including reduced risk of autoimmune diseases (133), diabetes mellitus type 2 (134), adverse pregnancy and birth outcomes (135), respiratory tract infections (136), and all-cause mortality rate (137). Whether vitamin D reduces risk of cardiovascular disease is still uncertain based on support from observational studies but not clinical trials (138). Thus, raising 25(OH)D concentrations in an effort to reduce cancer risk will yield additional benefits.…”
Section: Summary Tablementioning
confidence: 99%
“…Many other health benefits are associated with higher 25(OH)D concentrations, including reduced risk of autoimmune diseases (133), diabetes mellitus type 2 (134), adverse pregnancy and birth outcomes (135), respiratory tract infections (136), and all-cause mortality rate (137). Whether vitamin D reduces risk of cardiovascular disease is still uncertain based on support from observational studies but not clinical trials (138). Thus, raising 25(OH)D concentrations in an effort to reduce cancer risk will yield additional benefits.…”
Section: Summary Tablementioning
confidence: 99%
“…Humans obtain vitamin D from exposure to sunlight, diet and dietary supplements (1,2) . Although there is no consensus on optimal 25-hydroxyvitamin D (25(OH)D) concentrations as measured in serum, vitamin D deficiency (VDD) is commonly defined as a 25(OH)D concentration of <50 nmol/l (20 ng/ml) (1)(2)(3)(4) . This cut-off is the point where parathyroid hormone (PTH) starts to rise, which is the physiological definition of VDD (1) , although vitamin D supplementation (e.g.…”
mentioning
confidence: 99%
“…For example in a recent review article, it has been reported that VDBP polymorphism may affect the binding affinity for vitamin D, thereby, increasing the risk of vitamin D deficiency and other CVDs. 22 Lafi et al have also reported an association of VDBP polymorphism with increased risk of vitamin D deficiency among healthy Jordanians. 23 On the other hand, Michos et al showed that low serum levels of 25(OH)D were associated with increased incidence of CHD among Whites, however, no interaction of 25(OH)D levels with VDBP genotypes was found in that population.…”
Section: Discussionmentioning
confidence: 95%